2019
DOI: 10.1177/1074295619835190
|View full text |Cite
|
Sign up to set email alerts
|

Active Supervision: Preventing Behavioral Problems Before They Occur

Abstract: The current body of research on classroom environments identifies key proactive instructional strategies that when implemented effectively can reduce the likelihood of problematic behavioral incidents by students. One strategy known as active supervision has demonstrated positive outcomes across school settings, including classrooms, hallways, cafeterias, and playgrounds. In this article, authors provide a definition of active supervision, empirical support for its use, a detailed description of how to impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The findings of this study can be related to a study that, being attentive encompassed a supervisor's level of engagement with a child, which ranged from direct visual contact with the child to having no visual contact with the child [15]. To maintain attentive supervision, a similar confirmed that, such practice includes constant turning and head swiveling, as well as frequent glances around the room [25].…”
Section: Discussion On Teachers Supervision Of Kindergarten Learnerssupporting
confidence: 62%
See 2 more Smart Citations
“…The findings of this study can be related to a study that, being attentive encompassed a supervisor's level of engagement with a child, which ranged from direct visual contact with the child to having no visual contact with the child [15]. To maintain attentive supervision, a similar confirmed that, such practice includes constant turning and head swiveling, as well as frequent glances around the room [25].…”
Section: Discussion On Teachers Supervision Of Kindergarten Learnerssupporting
confidence: 62%
“…In difficult situations, children will benefit from observing their peers' play and anticipating what may happen next [23][24][25]. Teacher supervision is the act of directing and watching over the performance and activities of the children in your care.…”
Section:  Knowledge Of the Children In Care As Well As An Understand...mentioning
confidence: 99%
See 1 more Smart Citation
“…Active supervision (moving, scanning, and interacting) promotes on-task behavior and minimizes off-task behavior in a variety of settings (Haydon et al, 2019; Lewis et al, 2000). Throughout the day and, especially during challenging routines (e.g., transitions between activities), move among students, scan the room frequently, and provide frequent specific feedback to promote engagement and support student behavior.…”
Section: How Do Effective Educators Implement and Differentiate Universal Pbis To Support Students?mentioning
confidence: 99%